Treatment of Marigold Flower Processing Wastewater Using a Sequential Biological- Electrochemical Process - Akula, Lokesh Kumar; Oruganti, Raj Kumar; Bhattacharyya, Debraj; Kurilla, Kiran Kumar (Applied Science and Engineering Progress, 2021)
Agriculture is the mainstay of the Indian economy. The agro-based industries produce high volumes of highstrength wastewaters that need to be treated and reused to prevent environmental pollution and water wastage. This study evaluated the performances of a sequential biological-electrochemical process for treating an anaerobically digested effluent of a Marigold flower processing agro-industry. The uniqueness of this wastewater possess a major challenge to its treatment since not many studies have been conducted on this wastewater. The biological treatment was carried out in a Sequential Batch Reactor (SBR). The treated water was further polished in a Continuous Bipolar-mode Electrochemical Reactor (ECR) to remove the residual organics. The anaerobically digested effluent Chemical Oxygen Demand (COD), Dissolved Organic Carbon (DOC), Total Nitrogen (TN), Total Phosphorus (TP) and Total Suspended Solids (TSS) were 5750 ± 991 mg/L, 980 ± 120 mg/L, 692 ± 60 mg/L, 9.7 ± 1.1 mg/L, and 1144 ± 166 mg/L, respectively. A significant level of treatment was achieved in the SBR. The combined system was able to remove 79% of COD, 85% of DOC, 53% of TN, and almost 100% of TP, TSS, and Volatile Suspended Solids (VSS). Several organic compounds belonging to the category of natural plants compound, pesticide, fungicide, etc. were detected in the raw wastewater. Most of the compounds were almost completely removed by the treatment system. The final effluent was almost colorless and free from suspended solids. However, for reuse, the water needs to be further treated in an advanced oxidation process.